2022
DOI: 10.1093/ajcn/nqac259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal nutritional supplements on gestational weight gain in low- and middle-income countries: a meta-analysis of individual participant data

Abstract: Background Gestational weight gain (GWG) below or above the Institute of Medicine (IOM) recommendations has been associated with adverse perinatal outcomes. Few studies have examined the effect of prenatal nutrient supplementations on GWG in low- and middle-income countries (LMICs). Objectives To investigate the effects of multiple micronutrient supplements (MMS) and small-quantity lipid-based nutrient supplements (LNS) on GW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…First, the mother-infant pairs in our cohort study derived from the prenatal cluster-randomized controlled trial, in which pregnant women received micronutrient supplementation (folic acid, IFA, and MMN), and consequently the generalization of the results might be limited. Recently, a meta-analysis of IPD among LMICs showed that maternal MMN supplementation was associated with greater GWG percentage adequacy of GWG (defined by IOM according to total GWG) than was iron and folic acid only [ 37 ]. Therefore, the intervention in our study might reduce the percentage of inappropriate GWG.…”
Section: Discussionmentioning
confidence: 99%
“…First, the mother-infant pairs in our cohort study derived from the prenatal cluster-randomized controlled trial, in which pregnant women received micronutrient supplementation (folic acid, IFA, and MMN), and consequently the generalization of the results might be limited. Recently, a meta-analysis of IPD among LMICs showed that maternal MMN supplementation was associated with greater GWG percentage adequacy of GWG (defined by IOM according to total GWG) than was iron and folic acid only [ 37 ]. Therefore, the intervention in our study might reduce the percentage of inappropriate GWG.…”
Section: Discussionmentioning
confidence: 99%
“…We used individual characteristics, including current gestational weight, current gestational age, and height, as potential predictors. We developed the equation using the GWG Pooling Project data, which combined data from 55 studies and approximately 150,000 pregnant women in LMICs [ 28 , 29 ]. The GWG Pooling Project has accumulated a wealth of data on longitudinal gestational weights, including pre-pregnancy weights from some studies and early-pregnancy weights from many studies [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…We developed the equation using the GWG Pooling Project data, which combined data from 55 studies and approximately 150,000 pregnant women in LMICs [ 28 , 29 ]. The GWG Pooling Project has accumulated a wealth of data on longitudinal gestational weights, including pre-pregnancy weights from some studies and early-pregnancy weights from many studies [ 28 , 29 ]. We conducted external validation of the tool using internal data from Ethiopia [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…weight gain, birth weight and may reduce preterm births (Keats et al, 2019;Liu et al, 2022), there is no evidence for childhood health benefits (Devakumar et al, 2016) and the potential benefits and/or harms for people in high-income countries remains inconclusive (Petry et al, 2020;Raghavan et al, 2018;Wolf et al, 2017). This aims of this study were as follows: (1) to describe the types of supplements taken in pregnancy by maternal characteristics; (2) identify whether supplement use and/or type affect alignment with nutrient target recommendations and plasma concentrations of folate, zinc, calcium, iodine and iron, and urine iodine levels; and (3) assess whether mean daily dose of supplemental nutrients could be predicted by certain maternal characteristics.…”
Section: Key Messagesmentioning
confidence: 99%